The Impact Analysis Of Stock Reminder Of Goods To Quality Company - Wandanaya, Anita Bawaiqki; Rahmasary, Dea (Pandawan, 2019)
In the development of technology today especially on the needs of information in the business world becomes very important in determining the progress of a company. Where good activity in a company or technology is very determined by the information available. In an enterprise data collection system The current running goods are still using Microsoft Excel to log out and go in goods. The current system still has many shortcomings and disadvantages such as requiring a long time to know the quantity of goods stock because the warehouse admin has to calculate directly the amount of physical stock, the occurrence of the difference The number of goods request with the expenditure of goods due to error calculation by warehouse admin, it takes a long time to make the report of raw material request and expense, causing the company's performance and quality to be Hampered. Based on the problem, it needs a reminder to help the staff admin of the stock to manage the demand and expenditure of raw materials to avoid the difference in stock raw materials.